Plan de marketing social para el Museo Santa Catalina de Siena ubicado en el Centro Histórico de la Ciudad de Quito - Bravo Alarcón, Diana Paola (2014)
The museums in Ecuador have been cultivating the idea of keeping all artistic expression and every day that man has done, with the vision of eternizarlos over time and generations inherit to study and safekeeping as testify the Cultural Heritage cultural essence of our people. The Monastery of Saint Catherine of Siena covers art, culture and tradition of the Quito School representative, who was unable to have the same running time that has no nearby museums a large influx of visitors, causing ignorance of the wonders that this place and the lack of funding for social work, which is affected in terms of competitiveness, development and empirical administration is handled by the Sisters of the Monastery.